ISOLASI DAN KARAKTERISASI SELULOSA MIKROKRISTAL DARI AMPAS TEBU (SACCHARUM OFFICINARUM L.) - Nawangsari, Desy (Pharmacon: Jurnal Farmasi Indonesia, 2019)
Microcrystalline cellulose is the result of isolation from alpha cellulose. Woody plants are generally the source of microcrystalline cellulose production. One of the natural ingredients that can be used to make microcrystalline cellulose is bagasse (Saccharum officinarum L.). Bagasse contains 37.65% of cellulose which can be isolated by the delignification stage using a base solution, the process of bleaching and hydrolysis of alpha cellulose by high temperature heating using dilute dilute acid. The yield of microcrystalline cellulose from bagasse 26.03% and fulfilling the characterization based on the literature.